Six new and a little-known species of Rudgea (Rubiaceae—Palicoureeae) from the Guianas - Lachenaud, Olivier; Bruniera, Carla P.; Zappi, Daniela C. (Phytotaxa, 2022)
The Neotropical genus Rudgea (Rubiaceae) includes at least 120 species, 18 of which have previously been reported from the Guianas. While revising the material for the Flora of the Guianas, the authors uncovered and hereby describe six new species: R. approuaguensis, R. glomerulata, R. graniticola, R. itoupensis, R. jadinii and R. leucocarpa. Most of these are endemic to French Guiana, except R. graniticola which also occurs in Suriname, and R. leucocarpa, recorded also from Suriname and northern Brazil. Additionally, the original description of Rudgea ayangannensis, endemic of Guyana, is emended as it was based on a mixture of two different species, and adjustments are provided in a new description.